2022
DOI: 10.1002/ejoc.202101308
|View full text |Cite
|
Sign up to set email alerts
|

From Biomass to the KarrikinsviaSelective Catalytic Oxidation of Hemicellulose‐Derived Butyl Xylosides and Glucosides

Abstract: Members of the karrikin family of bioactive small molecules are known to promote germination of a range of plants following large scale fires. As a result, they are relevant and interesting compounds. This report describes their synthesis from a biomass‐derived product stream. During work to fractionate biomass with the goal of obtaining high quality lignins, an interesting co‐product stream derived from the hemicellulose in the biomass, was obtained. Whilst many applications of this co‐product stream can be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…We propose that steric interactions between the bulky L 3 ligand and glycoside substrates may overcome intrinsic electronic factors that favor oxidation at C3 . The dependence of chemoselectivity on the ligand structure observed here therefore offers an opportunity to obtain rare oxidized glycosides, which can undergo further functionalization to yield valuable carbohydrate products. , …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…We propose that steric interactions between the bulky L 3 ligand and glycoside substrates may overcome intrinsic electronic factors that favor oxidation at C3 . The dependence of chemoselectivity on the ligand structure observed here therefore offers an opportunity to obtain rare oxidized glycosides, which can undergo further functionalization to yield valuable carbohydrate products. , …”
Section: Resultsmentioning
confidence: 86%
“…Chemoselective catalytic oxidation of alcohols is a powerful strategy for the sustainable production of fine and commodity chemicals with minimal time, waste, and cost. Air is a convenient and attractive terminal oxidant, but partially reduced oxygen can generate highly active species that participate in competitive, nonselective reactions. , We previously reported that the dimeric cationic palladium complex [( L 1 )­Pd­(μ-OAc)] 2 [OTf] 2 ( L 1 = neocuproine = 2,9-dimethyl-1,10-phenanthroline) is an effective catalyst precursor for the oxidation of vicinal polyols under mild conditions to afford α-hydroxyketones with high regio- and chemoselectivities. This catalyst is also selective for the direct oxidation of carbohydrates to 3-ketoses, , a complex transformation that typically demands multiple steps of protection/deprotection. , However, under aerobic conditions, H atom abstraction and subsequent oxidation of the benzylic methyl C–H bonds on the neocuproine ligand generate inactive palladium carboxylate species (Figure A, species 1** ). ,, This competitive ligand oxidation limits catalyst lifetime and necessitates high palladium loadings to achieve high conversions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, butenolide-based structures have received considerable interest. γ-Methylenebutenolides are a relevant subclass because of their interesting biological activity 7 and versatility as synthetic intermediates. 8 However, despite remarkable examples such as a palladium-catalyzed cyclocarbonylation of aryl halides with acetylenes (Scheme 1c) 9 b and a gold-catalyzed synthesis starting from propargyl diazoacetates (Scheme 1d), 9 c the preparation of butenolides bearing the exo -methylene moiety is less explored.…”
Section: Introductionmentioning
confidence: 99%